A LITERATURE REVIEW ON THE DETERMINANTS OF CUSTOMER SATISFACTION - Resti Hardini; Rahayu Lestari; Suadi Sapta Putra; Kumba Digdowiseiso; Zuha Rosufila Abu Hasan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The literature review investigates the factors that determine customer satisfaction, specifically in the life insurance and banking industries. This study highlights the intricate nature of swiftly evolving market dynamics, wherein elements like corporate reputation, service excellence, and perceived worth exert a substantial influence on customer contentment. The approach employed entails a methodical examination of the existing body of literature, elucidating the interconnectedness among variables that exert an impact on customer satisfaction. The research findings indicate that customer satisfaction is primarily influenced by service quality and company image, with perceived value playing a pivotal role in this process. The difficulties associated with assessing customer perceptions and addressing feedback underscore the necessity for the creation of meticulous measurement techniques and efficient response mechanisms. Ultimately, comprehending these factors thoroughly is crucial for devising efficient tactics to fulfill customer expectations and facilitate sustainable business expansion. Additionally, it emphasizes the importance of persistent dedication and ongoing enhancement.